A WIRELESS POWER TRANSFER SYSTEM DESIGN USING TRANSMITTER LARGER THAN RECEIVER FOR MOBİLE PHONES (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
In a world where technology grows rapidly, electrical energy is of vital importance. In the recent future, the wireless transmission of electrical energy is expected to play a vital role in our lives. This paper investigated a Wireless Power Transfer (WPT) system with a transmitter size larger than the receiver size. Magnetic resonance coupling was used as the WPT system. Wireless charging of mobile phones was realized with a large transmitter coil and a small receiver coil placed on the back of the mobile phone. In this study, the WPT system was designed for a frequency of 1 MHz and a power of 5 W. As a result of the calculations and simulations made for the WPT system, an efficiency of 97 % was obtained in a 10 mm air gap. Analyzes were made according to the different receiver and transmitter coil sizes and air gaps. The optimal coil size has been determined. Air gap and misalignment limits are determined for optimal coil size. The analytical calculations and modeling of the design are made for the best efficiency and the most suitable receiver and transmitter coil design in Serial-Series (SS) topology. Wireless phone charging design was carried out using various programs. In addition, the effects of the design on human health were examined.
Keywords: Wireless power transfer; Magnetic resonance coupling; Mobile phone; Efficiency; Coupling factor